Lições sobre a sintaxe histórica do infinitivo português (Caligrama: Revista de Estudos Românicos, 2012)
Resumo: Exponho a sintaxe histórica do infinitivo final e do infinitivo objetivo do português, partindo da sintaxe histórica do infinitivo latino. Este, originalmente forma nominal pura, isto é, ablativo ou dativo de nome de ação, emprega-se como adjunto adverbial de finalidade. Tratado posteriormente como nome neutro indeclinável, passa a construir-se como objeto direto. Ilustro a exposição com exemplos de autores da língua latina e portuguesa; em particular da Demanda do Santo Graal e de Os Lusíadas de Camões.Palavras-chave: Sintaxe histórica do infinitivo português; infinitivo final; infinitivo objetivo.Abstract: I deal with the historical syntax of the infinitive of purpose and complementary infinitive in Portuguese. In order to do that, I begin with the historical syntax of the Latin infinitive. This infinitive originally is a pure noun form, or rather, an ablative or dative of an action name, so that it is used to indicate the purpose of the verbal action. It subsequently is treated as an indeclinable neuter noun, so that it completes the meaning of a verb. I illustrate my exposition by quoting from many authors in Latin and in Portuguese, mostly, from the Demanda do Santo Graal and Camões’ Os Lusíadas.Keywords: Historical syntax of Portuguese infinitive; infinitive of purpose; complementary infinitive.